Legal Inconsistencies in Sea Sand Export Re-permits: A Constitutional Perspective on Regulatory Hierarchy - Aristo, Erly; Melvern, Davelyn; Senjaya, Johanes (As-Siyasi: Journal of Constitutional Law, 2026)
Government Regulation No. 26 of 2023 on Marine Sedimentation Management has sparked significant legal and ecological controversy by re-authorizing sea sand exports. This study examines the regulation's compatibility with Law No. 32 of 2009 on Environmental Protection and Management, the Sustainable Development Goals (SDGs), and constitutional principles regarding the hierarchy of norms. Employing a normative juridical method with statutory and conceptual approaches, the research identifies a clear conflict of norms (lex superior derogat legi inferiori). The findings demonstrate that the regulation substantively permits activities inconsistent with the ecological protection mandates established in Law No. 32 of 2009. This dualism, combining ecological justification with commercial export interests, creates legal uncertainty and violates the principle of normative hierarchy. Furthermore, the policy manifests as ecological injustice, characterized by inadequate protection of coastal communities, limited public participation, and a lack of transparency. The study concludes that these inconsistencies constitute a structural legal defect rather than a mere policy shift. Consequently, legal reform at the statutory level is necessary to ensure conformity with superior legal norms, strengthen legal safeguards for affected communities, and realign environmental governance with constitutional principles and international sustainable development commitments.